A Novel Hybrid Symmetric Key Encryption Algorithm for Telegu Script - Madhavi Kumari, T; Vinaya Babu, A (International Journal of Computer Sciences and Engineering, 2021)
Technology is the key to innovation in all aspects of this modern age. In any technology, data becomes the most important asset to protect. Many encryption algorithms are widely available and used in information security. Encryption can provide secure information across the platform. Encrypting the message using natural languages reduces encryption time and improves performance. Telugu is the oldest Dravidian language spoken in South India. The message to be encoded is translated into Telugu, after which this translated text is converted into a randomly generated combination of 2-bit English alphabets. This is a hybrid algorithm because the intermediate node is encrypted using the standard advanced encryption algorithm to improve the privacy of the text. Because Telugu encryption method uses three phases, namely translation, mapping, and encryption, this makes the data much more secure than existing algorithms like Blowfish and Data Encryption Standard (DES), and the person trying to decrypt must have knowledge of the Telugu language, as well as mapping details to see the original data and This algorithm shows a stronger avalanche effect of 96.5%, which is greater than Blowfish and DES. Evaluation of the proposed algorithm shows that it runs faster and has relatively less encryption time, less memory requirements.